PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS SCIENTIFIC APPROACH UNTUK MEMBANGUN KARAKTER KEPEDULIAN DAN KEDISIPLINAN - Purnamasari, Veryliana; Nur Wangid, Muhammad (Jurnal Pendidikan Karakter, 2016)
Abstrak: Penelitian ini bertujuan menghasilkan perangkat pembelajaran berbasis scientific approach Keindahan Alam Negeriku yang layak bagi kelas IV SD untuk membangun karakter kepedulian dan kedisiplinan dan mengetahui keefektifannya. Penelitian ini merupakan penelitian dan pengembangan yang mengacu pada model Borg & Gall. Subjek uji coba siswa kelas IV SDN Salamrejo Sentolo, Kulon Progo. Subjek uji coba awal terdiri atas 4 siswa. Subjek uji coba lapangan terdiri atas 10 siswa yang belum terlibat dalam uji coba awal, dan subjek uji lapangan operasional terdiri atas 39 siswa dari kelas IVA dan kelas IVB. Hasil penelitian berupa perangkat pembelajaran yang meliputi: silabus, RPP, LKS, dan instrumen penilaian. Hasilnya menunjukkan perangkat pembelajaran yang telah dikembangkan layak menurut ahli materi dan ahli pembelajaran dengan kategori penilaian sangat baik. Perangkat pembelajaran dinilai efektif karena hasil uji t pada karakter peduli sebesar 4,854 dan karakter disiplin sebesar 1,926 lebih besar dari t table yaitu 1,684 sehingga menunjukkan ada perbedaan yang signifikan terhadap karakter disiplin dan peduli antara siswa yang mengikuti pembelajaran tanpa perangkat pembelajaran dan yang menggunakan perangkat pembelajaran hasil pengembangan. Kata Kunci: pengembangan, perangkat pembelajaran, scientific approach, karakter LEARNING SOFTWARE DEVELOPMENT BASED ON SCIENTIFIC APPROACH TO BUILD CHARACTER OF CARE AND DISCIPLINE Abstract: This study aims to (1) produce a learning device based on scientific approach that can be feasible to develop the character of elementary school fourth graders especially caring and discipline character and (2) determine the effectiveness of learning device based on scientific approach that can develop the character of elementary school fourth graders especially caring and discipline character. This was a research and development (R & D) study consisting of ten stages, namely: (1) preliminary study and data collection, (2) planning, (3) product draft development, (4) preliminary field tryout, (5) revision of the tryout result, (6) field tryout, (7) product finalization based on the field tryout result, (8) operational field testing, (9) final product finalization and (10) dissemination and implementation. The tryout subjects were Grade IV students of SDN Salamrejo Sentolo Kulon Progo. The preliminary field tryout subjects consisted of four students. The main field testing subjects consisted of ten students who were not involved in the preliminary field tryout. The operational field tryout subjects consisted of 39 students from Grade IV A and Grade IV B.The result of this research is a learning device consisting of a syllabus, lesson plans, student worksheets, and assessment instruments. The resultsof expert show that the learning device has been developed is feasible according to the material expertand learning expert with excellent assessment category.The device is also consid ered an effective learning because the results of the t test on the character of caring are 4.854, in the character of the discipline 1.926 which greater than t table is 1.684 indicating significant difference of the character of discipline and care among the students who follow the teaching and learning and those without using learning device. Keywords: development, learning device, scientific approach, characters